2010
DOI: 10.1614/ws-d-09-00046.1
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Translocation of Glyphosate, Metsulfuron, and Triclopyr in Old World Climbing Fern (Lygodium microphyllum)

Abstract: Old World climbing fern is one of the most invasive plants in natural areas of central and southern Florida. The fern spreads across the landscape by wind-blown spores and invades isolated and undisturbed habitats such as interior portions of the Florida Everglades. Land managers in Florida have reported that multiple herbicide treatments are required to control the fern, which could indicate that herbicides do not translocate throughout the plant in long-established populations. We conducted a greenhouse stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 37 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Herbicide translocation was limited in OWCF, with the majority of the herbicide remaining at the spot of application (Hutchinson et al 2010). Treatment of OWCF with radiolabeled metsulfuron at a concentration of 270 mg ai L 21 (0.10 kg ai 370 L 21 ) indicated that 17.3%, or approximately 46.7 mg ai L 21 , of the applied herbicide remains at the spot of application.…”
Section: Resultsmentioning
confidence: 99%
“…Herbicide translocation was limited in OWCF, with the majority of the herbicide remaining at the spot of application (Hutchinson et al 2010). Treatment of OWCF with radiolabeled metsulfuron at a concentration of 270 mg ai L 21 (0.10 kg ai 370 L 21 ) indicated that 17.3%, or approximately 46.7 mg ai L 21 , of the applied herbicide remains at the spot of application.…”
Section: Resultsmentioning
confidence: 99%
“…Triclopyr amine treatments, even at high rates of 6.7 kg ae ha –1 (6 lb ae acre –1 ) resulted in excellent control of L. microphyllum with a concomitant increase in native vegetation and species richness (Hutchinson and Langeland 2007). In addition, triclopyr is absorbed more thoroughly by L. microphyllum at 60% when compared with the standard treatment of glyphosate at 31%, although most of the chemical remains in the leaves, showing minimal basipetal translocation regardless of the treatment (Hutchinson et al 2010).…”
Section: Introductionmentioning
confidence: 99%